(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, special attention is paid to the mental health of HIV-infectedadolescents, the content of the process of self-education and pedagogical- psychological aspects of selfeducation. As a result of education and family environment, the life goals and ideals of every teenager are formed. Self-education in the lives of HIV-infected adolescents is aimed at the correct acquisition of national ideas, a certain scientific outlook, community, political awareness and vigilance, strong beliefs and an active outlook on life (without stigma and discrimination).